Una professione plurale Il caso dell'avvocatura fiorentina - Alacevich, Franca (Studi e saggi, 2017)
Crisis, malaise and social fragmentation are recurring themes in the representation of the middle classes. The volume, based on the results of an investigation into the forensic profession carried out with the contribution of the Bar Council of Florence, delves into the issue by placing itself in a line of studies that has recently regained vigour within the Italian and international sociological debate. By touching on a plurality of themes and using mixed investigation methods, the research has allowed the authors to verify how different employment situations translate into an unequal distribution of life chances and into different attitudes towards profession, politics and social life, allowing also to explore the role played by lawyers in change processes.